(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO - 1. L’ente ecclesiastico: una figura soggettiva complessa - 2. Il diritto speciale nella disciplina dell’ente ecclesiastico - 3. La specialità derivante dal carattere bilaterale della normativa sugli enti: il caso emblematico della responsabilità amministrativa derivante da reato - 4. L’espansione del diritto comune nella disciplina dell’ente ecclesiastico - 5. La specialità di regime degli enti ecclesiastici nell’evoluzione dell’ordinamento - 6. Diritto speciale e diritto comune nella riforma del Terzo settore. Ecclesiastical bodies between special rules and general law ABSTRACT: This contribution examines the relationship between special law rules of a treaty nature and general law in the Italian discipline of civilly recognized ecclesiastical bodies, in particular those of the Catholic Church, which still represents most part of these entities. This aspect is examined with respect to the latest regulatory evolution, in particular the reform of the Third sector, which tends to confirm the duplicity of regime of ecclesiastical bodies. It also highlights the growing attention and protection of the normative peculiarities of this category of legal entities by the State legislator.